Risk factors of childhood constipation - Dyah Kurniati Dyah Kurniati (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2002)
Background: Despite it is not considered as a dangerous situation in children older than 2 years old, but attantion is important in young infant. Improper treatment in constipation may contributed to the raise of anxiety, emotionally disorder either for the children or its relatives.Objective: To determine what factors related to constipation in children.Design and Methods: A case control study was conducted for all of children who were admitted to ambulatory polyclinic and inpatient clinic of Sardjito Hospital during January 2001 - December 2001. A questionaire was obtained by the researcher or assistant by direct interview to the parents or guardian. Results: We enrolled 86 children, consisted of 43 children in constipation group and the 43 children as control. There was significant difference (p<0.01) when reported having toilet training disturbance, daily fluid intake, the variety of daily meals (vegetables, fruits) and sweetened foods. Relative risk of having constipation due to toilet training disturbance in constipations group is 0.14 (CI: 0.06 - 0.38).Conclusion: Toilet training disturbance, daily fluid intake, the variability of daily meals and sweetened foods are risk factors of constipation in childhood. Key words: children - constipation - clinical findings - risk factors